Non-revenue water reduction strategies: a systematic review - Farouk, Abdelrahman M.; Rahimi, A. Rahman; Noor Suraya, Romali (Emerald Publishing Limited, 2021)
Purpose Sustainability involves ensuring that sufficient resources are available for current and future generations. Non-revenue water (NRW) creates a barrier to sustainability through energy and water loss. However, a comprehensive overview of NRW reduction strategies is lacking. This study reviews the existing literature to identify available strategies for reducing NRW and its components and discusses their merits.